Silk fibroin microspheres with uniform particle size as well as preparation method and application of silk fibroin microspheres

Silk fibroin microspheres were prepared by membrane emulsification and multiple microsphere crystallization, which solved the problems of uneven particle size and rough surface, and enabled efficient and low-cost large-scale production, producing silk fibroin microspheres with uniform particle size and smooth surface.

CN121021874AActive Publication Date: 2025-11-28FAVORSUN MEDICAL TECH (SUZHOU) CO LTD

Patent Information

Application Number
CN202511548441.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-28
Publication Date
2025-11-28
Estimated Expiration
2045-10-28

AI Technical Summary

Technical Problem

Existing technologies struggle to prepare silk fibroin microspheres with particle sizes between 20 and 100 μm, high uniformity in particle size distribution, good sphericity, and smooth surfaces. Furthermore, traditional methods suffer from high preparation costs and low throughput.

Method used

Using modified silk fibroin raw materials, silk fibroin microspheres were prepared through membrane emulsification and multiple microsphere crystallization methods, combined with cross-linking agents and crystallization inducers. The process included steps such as enzymatic modification, membrane emulsification, cross-linking reaction, and vacuum freeze-drying, controlling the particle size and crystallinity of the microspheres.

Benefits of technology

Silk fibroin microspheres with uniform particle size, smooth surface, and high crystallinity were prepared, which improved the microsphere yield, made them suitable for large-scale production, and enhanced the safety and application effect of the microspheres.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121021874A_ABST
    Figure CN121021874A_ABST
Patent Text Reader

Abstract

The invention discloses uniform-particle-size silk fibroin microspheres and a preparation method and application thereof.The preparation method comprises the following steps that a regenerated silk fibroin solution is taken and subjected to trypsin digestion to obtain modified silk fibroin sediment, and the modified silk fibroin sediment is dissolved in an aqueous solution of a beta-folding inhibitor to obtain a silk fibroin solution serving as a dispersed phase; emulsifying through an external pressure type membrane emulsifier to obtain an emulsion containing the silk fibroin emulsion droplets; adding a cross-linking agent into the emulsion to carry out cross-linking reaction, and then adding a crystallization inducer to induce crystallization to obtain primary silk fibroin microspheres; and performing vacuum freeze drying to obtain the silk fibroin microspheres. Silk fibroin is subjected to enzyme digestion modification, silk fibroin fragments with high beta-folding content are reserved, and high structural stability is achieved; the crystallinity of the microspheres is improved by adopting a membrane emulsification mode and combining a multiple crystallization induction method, and the silk fibroin microspheres with uniform particle size and smooth surfaces are obtained.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of silk fibroin microsphere preparation, and particularly relates to a silk fibroin microsphere with uniform particle size, a preparation method and application thereof. BACKGROUND

[0002] Silk fibroin is a natural polymer material extracted from silk, which has good mechanical properties, biodegradability and low immunogenicity, and high biocompatibility, and has a wide range of application scenarios in the fields of biological regenerative medical materials, cosmetics and pharmaceutical industry. The molecular structure of silk fibroin is composed of highly ordered beta-sheet crystalline regions and loose disordered amorphous regions. Among them, the crystalline region is mainly composed of hydrophobic small molecule amino acid residues such as glycine, alanine and serine, which are repeatedly arranged to form a tightly packed antiparallel beta-sheet lamellar structure, which gives silk fibroin excellent mechanical strength and stability; and the amorphous region has a high content of hydrophilic amino acids, which can adjust the hydrophilic and hydrophobic properties of silk fibroin and inhibit the assembly of the beta-sheet crystalline region.

[0003] Silk fibroin microspheres are biodegradable, and the degradation products are amino acids, which have no irritation and can be absorbed by the body, and are a potential alternative material for filling medical products and cosmetic products. The particle size, sphericity and surface smoothness of the microspheres have a significant impact on their efficacy. If the particle size of the microspheres is too small (usually <20 μm), they will be phagocytosed by macrophages and cause strong inflammation, and if the particle size is too large, the filling particles will be obvious and the risk of vascular embolism will be high. The particle size of the microspheres commonly used in skin fillers is between 20-100 μm, and the more uniform the particle size, the higher the sphericity and the smoother the surface, the smaller the inflammation caused by the implanted local tissue and the higher the safety.

[0004] The current common methods for preparing silk fibroin microspheres include low-temperature freeze crystallization, electrospray, emulsification and microfluidic method, etc. The silk fibroin microspheres prepared by freeze crystallization and electrospray will have low particle size and high surface roughness due to ice crystal formation or rapid liquid evaporation. Although the conventional mechanical emulsification method can prepare silk fibroin microspheres with smooth surface, the particle size uniformity is low, and the low yield after screening leads to high cost of microsphere preparation. The microfluidic method can prepare microspheres with uniform particle size, but its throughput is low and it is difficult to produce on a large scale.

[0005] Patent CN114874466A discloses a silk fibroin microsphere, a preparation method and application thereof. The silk fibroin solution containing an ionic dispersant and a sphere-forming agent is treated by low-temperature coagulation to prepare a silk fibroin microsphere solution, and then diluted, subjected to wet heat crystallization treatment and spray dried to prepare a solid silk fibroin microsphere. However, this method can only prepare microspheres with a particle size of about 2 μm.

[0006] Patent CN119331274A discloses a preparation method of silk fibroin nanospheres. First, a crystallization inducer is directly added to a silk fibroin solution, mixed uniformly, and then a gelatin solution is added to the solution as a dispersant. After mixing, a pretreated liquid is obtained. Then, the pretreated liquid is prepared into silk fibroin nanosphere liquid through low-temperature coagulation and ultrasonic dispersion. Finally, the silk fibroin nanosphere liquid is centrifuged and freeze-dried to obtain solid silk fibroin nanospheres. On the one hand, this method can only prepare silk fibroin microspheres with an average diameter of about 260 nm, limiting the application range. On the other hand, most of the microspheres observed under an electron microscope are found to be adhered, and the surface of the microspheres is very rough, and the particle size is not uniform.

[0007] Patent CN117304519A discloses a preparation method of silk fibroin microspheres and silk fibroin microspheres. At 35-60℃, silk fibroin solution is added dropwise to a mixed oil phase containing liquid paraffin, Span 80 and Tween 80 under stirring, and stirring is continued for 30-90 min. After separation, silk fibroin microspheres with a particle size of 20-80 μm are obtained. However, the silk fibroin microspheres prepared by this method have poor sphericity, and rapid solidification after ethanol washing leads to serious shrinkage of most of the microspheres.

[0008] Patent CN118420936A discloses a silk fibroin microsphere and a preparation method thereof. Silk fibroin is dissolved with a dissolving solution and then chemically modified with a modifier to obtain a silk fibroin stock solution. An excipient is added to the silk fibroin stock solution to obtain a silk fibroin pre-solution. The silk fibroin pre-solution is prepared into silk fibroin microspheres with adjustable size by microfluidic method. An enhancer is added to the silk fibroin microspheres with adjustable size to obtain silk fibroin microspheres with excellent mechanical properties. The microfluidic technology used in this method can prepare microspheres with a particle size of about 60 μm. However, the microfluidic technology has low throughput, making it difficult to scale up for production, and some of the prepared microspheres are adhered, and some of the microspheres have wrinkles on the surface.

[0009] In summary, there is still a great challenge in how to prepare silk fibroin microspheres with a particle size of 20-100 μm, high uniformity of particle size distribution, good sphericity and smooth surface. SUMMARY

[0010] The present application provides a uniform particle size silk fibroin microsphere, a preparation method thereof and an application, which uses modified silk fibroin raw material, membrane emulsification and multiple microsphere crystallization to prepare silk fibroin microspheres with a particle size of 20-100 μm, uniform particle size and smooth surface.

[0011] To solve the above technical problems, the present application provides a preparation method of uniform particle size silk fibroin microspheres, comprising the following steps: S1, taking regenerated silk fibroin solution, and obtaining modified silk fibroin precipitate by trypsin enzymolysis, and dissolving the modified silk fibroin precipitate in a water solution of a beta-sheet inhibitor to obtain a silk fibroin solution as a dispersed phase; S2, dispersing the dispersed phase in a continuous phase by an external pressure membrane emulsifier to obtain an emulsion containing silk fibroin emulsion droplets; S3, adding a crosslinking agent to the emulsion to perform a crosslinking reaction of the silk fibroin, and then adding a crystallization inducer to induce crystallization of the silk fibroin to obtain silk fibroin primary microspheres; S4, vacuum freeze-drying the silk fibroin primary microspheres to obtain silk fibroin microspheres.

[0012] Based on the hydrophilic non-crystalline region existing in the silk fibroin, the crystallization effect is affected when preparing the silk fibroin microspheres, thereby causing poor sphericity of the microspheres and a rough surface. The silk fibroin is modified by enzymolysis in the application, the hydrophilic sites in the non-crystalline region are removed, and the raw material mainly retains the silk fibroin fragments with high beta-sheet content of the repeated GAGAS sequence, which has high structural stability. Compared with the unmodified silk fibroin, the modified silk fibroin is more easily induced to form microspheres, and the prepared microspheres have better sphericity, higher crystallinity, smoother surface and better resistance to enzymolysis.

[0013] The membrane emulsification method is adopted in the application, which can prepare microspheres with more uniform particle size and higher yield, and is more conducive to scale-up production. At the same time, the crystallinity of the microspheres is improved by combining a multiple crystallization induction method. First, the crosslinking agent is used to crosslink the emulsion droplets after emulsification, which narrows the distance between the silk fibroin molecular chains to form crystalline nuclei. Then, the crystallinity of the microspheres is improved by treating with a crystallization inducer and vacuum freeze-drying. In the vacuum freeze-drying process, the freeze-drying process of rapid freezing and low-temperature sublimation is used to control the rate of water evaporation in the microspheres. Compared with the traditional freeze-drying process, the surface of the microspheres is smoother and the structure is more compact.

[0014] Further, in S3, the crosslinking agent is one or more of butanediol glycidyl ether (BDDE), divinyl sulfone (DVS), and Epoxide-PEG-Epoxide (molecular weight: 1kDa-20kDa), and preferably butanediol glycidyl ether; And / or, the volume ratio of the crosslinking agent to the dispersed phase is 0.5%-5%; And / or, the crosslinking reaction conditions are as follows: temperature: 30-80℃, preferably 40-60℃; stirring speed: 150-500rpm, preferably 250-400rpm; time: 20-90min, preferably 30-60min.

[0015] Further, in S3, the crystallization inducer is one or more of methanol, ethanol, isopropanol, n-butanol, t-butanol, acetone, formic acid, N,N-dimethylformamide, dimethyl sulfoxide, chloroform, and ethylene oxide, preferably methanol; Further, the volume ratio of the crystallization inducer to the dispersed phase is 100%-800%; Further, the conditions for inducing the crystallization of the silk fibroin are as follows: temperature 30-80℃, preferably 40-60℃; stirring speed 150-500rpm, preferably 250-400rpm; and time 2-10h, preferably 5-8h.

[0016] Further, in S3, after inducing the crystallization of the silk fibroin, the upper liquid is discarded, and the lower silk fibroin primary microspheres are washed: water washing 3 times, ethyl acetate washing 3 times, petroleum ether washing 3 times, ethyl acetate washing 3 times, and water washing 3 times, with ultrasonic treatment during washing.

[0017] Further, in S2, the membrane tube of the external pressure membrane emulsifier is an SPG membrane, and the membrane pore size is 5-40μm, preferably 10-20μm. Further, the parameters of the emulsification are as follows: temperature 5-30℃, preferably 10-20℃; continuous phase flow rate 0.5-1.5m / s, preferably 0.8-1.2m / s; membrane pressure 0.5kPa-5kPa, preferably 1.0kPa-2.5kPa; and volume / mass ratio of the dispersed phase to the continuous phase 10%-50%, unit mL / g.

[0018] Further, in S2, the mass / volume ratio of the silk fibroin to the aqueous solution in the dispersed phase is 2%-25%, preferably 5%-15%, unit g / mL. Further, the continuous phase is one or more of light liquid paraffin, heavy liquid paraffin, soybean oil, castor oil, palm oil, olive oil, sesame oil, corn oil, lecithin, petroleum ether, n-hexane, n-heptane, vaseline, silicone oil, and ozokerite, preferably light liquid paraffin. Further, the continuous phase further comprises a surfactant with a mass concentration of 0.5%-3%, preferably 1%-1.5%.

[0019] Further, the surfactant is one or more of Tween 20, Tween 40, Tween 60, Tween 80, Tween 85, 3-[(3-cholamidopropyl)dimethylammonio]-1-propanesulfonic acid (CHAPS), 3-sulfopropyl n-tetradecyl dimethyl ammonium, Span 20, Span 40, Span 60, Span 80, Span 85, sodium dodecyl sulfonate, sodium dodecyl sulfate (SDS), sodium dodecyl benzene sulfonate, polyvinyl alcohol, polyvinyl pyrrolidone, polyoxyethylene stearyl alcohol ether, polyglycerol fatty acid ester, calcium abietate, magnesium stearate, sorbitan palmitate.

[0020] Further, in S4, the vacuum freeze-drying comprises the following steps: cooling at a rate of 0.4-1℃ / min to 0-4℃ for 20-40min; cooling at a rate of 0.9-1.2℃ / min to -50℃ ~ -40℃ for 60-120min; warming to -20℃ ~ 0℃, sublimating for 10-24h under a vacuum of 0-30Pa; warming to 0-30℃, drying for 5-30h under a vacuum of 0-30Pa.

[0021] The rapid cooling during vacuum freeze-drying can form more uniform and smaller ice crystals in the microspheres, preventing large ice crystals from being produced by slow crystallization and causing pits on the surface of the microspheres; and the low-temperature sublimation can make the ice crystals sublimate slowly, thereby reducing the shrinkage of the microspheres during sublimation.

[0022] Further, in S1, the weight average molecular weight of the regenerated silk fibroin is 50kDa-250kDa.

[0023] Further, in S1, the beta-sheet inhibitor is one or more of LiBr, NaSCN, ZnCl2, CaCl2, preferably LiBr. Further, the concentration of the beta-sheet inhibitor in the aqueous solution of the beta-sheet inhibitor is 4-9.3M, preferably 6-9.3M.

[0024] The second aspect of the application provides the silk fibroin microspheres prepared by the preparation method of the first aspect.

[0025] The third aspect of the application provides the use of the silk fibroin microspheres of the second aspect in medical products and cosmetic products.

[0026] The application has the following beneficial effects: The silk fibroin is subjected to enzymatic modification in the application, the hydrophilic sites in the non-crystalline region are cut off, the raw material mainly retains the silk fibroin fragments with high beta-sheet content of the repeated GAGAS sequence, has high structural stability, is easier to induce crystallization to form microspheres compared with the unmodified silk fibroin, and the prepared microspheres have better sphericity, higher crystallinity and smoother surface, and are more resistant to enzymatic hydrolysis.

[0027] The membrane emulsification method is adopted in the application, which can prepare microspheres with more uniform particle size, higher yield and more conducive to scale-up production; at the same time, the crystallinity of the microspheres is improved by combining multiple crystallization induction methods: firstly, the liquid droplets are crosslinked after emulsification by a crosslinking agent, the distance between the silk fibroin molecular chains is shortened to form crystalline nuclei, and then the crystallinity of the microspheres is improved by treating with a crystallization inducer and vacuum freeze drying.

[0028] In the vacuum freeze drying, the freeze drying process of rapid freezing cooling-low temperature sublimation method is adopted to control the rate of water evaporation in the microspheres, which can make the surface of the microspheres smoother and the structure more compact compared with the traditional freeze drying process. DETAILED DESCRIPTION

[0029] In order to more clearly illustrate the technical solutions of the application, the drawings needed in the embodiments will be briefly introduced below, and obviously, the drawings in the following description can also be used to obtain other drawings without creative labor for those skilled in the art.

[0030] Figure 1 is the SEM diagram of the silk fibroin microspheres obtained in Example 1 of the application; Figure 2 is the SEM diagram of the silk fibroin microspheres obtained in Example 5 of the application; Figure 3 is the SEM diagram of the silk fibroin microspheres obtained in Comparative Example 1 of the application; Figure 4 is the SEM diagram of the silk fibroin microspheres obtained in Comparative Example 2 of the application; Figure 5 is the SEM diagram of the silk fibroin microspheres obtained in Comparative Example 3 of the application; Figure 6 is the SEM diagram of the silk fibroin microspheres obtained in Comparative Example 4 of the application; Figure 7 is the degradation curve of the silk fibroin microspheres obtained in Example 1 and Comparative Examples 1-2 of the application. DETAILED DESCRIPTION

[0031] The technical solutions of the present application will be clearly and completely described below in combination with specific embodiments of the present application. Obviously, the described embodiments are only some of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative efforts belong to the protection scope of the present application.

[0032] Embodiment 1

[0033] This embodiment relates to a preparation method of silk fibroin microspheres with uniform particle size, comprising the following steps: (1) Dissolve 150 g of anhydrous sodium carbonate in 15 kg of water, and after boiling, add 150 g of silk, and cook for 45 min to obtain degummed silk. The degummed silk is fished out, washed with water for 3 times, and then dried. 50 g of the dried degummed silk is dissolved in 500 mL of 9.3 M LiBr solution, filtered, and purified by molecular weight screening to obtain a regenerated silk fibroin aqueous solution with a weight average molecular weight of 100 kDa-250 kDa, and an equal volume of trypsin solution of 3 mg / g is mixed, reacted at 37℃ for 20 h, and then heated at 100℃ for 10 min to inactivate the enzyme. The supernatant is removed by centrifugation at 5000 rpm for 10 min, and then dried to obtain a modified silk fibroin precipitate raw material.

[0034] (2) Dissolve 9.0 g of silk fibroin precipitate in 60 mL of 9.3 M LiBr aqueous solution until completely dissolved to prepare a 15% (w / v) silk fibroin solution as a dispersed phase.

[0035] (3) An external pressure type SPG membrane emulsifier is used, the dispersed phase is located outside the hydrophobic SPG membrane tube, and the continuous phase is located inside and continuously flows through a pump. External nitrogen is pressurized and directly acts on the outside of the membrane tube to automatically and continuously process and prepare silk fibroin emulsion droplets. Specifically, 60 mL of the silk fibroin solution prepared in step (2) is taken as the dispersed phase, cooled to 20℃ in an ice water bath, and then added to the dispersed phase storage tank; 4.5 g of Tween 80 is weighed and added to 300 g of light liquid paraffin continuous phase, stirred and mixed uniformly, and a cooling circulating pump is used to keep the continuous phase temperature at 20℃; the magnetic pump is turned on to make the continuous phase fill the inside of the membrane tube, the membrane pressure is set to 1.0 kPa, the nitrogen valve is opened, and the dispersed phase solution passes through the SPG membrane under the action of nitrogen pressure to prepare light liquid paraffin emulsion containing silk fibroin emulsion droplets. The emulsion is collected in a post-treatment kettle. The membrane tube specification is Φ10 mm x L125 mm (effective length 105 mm), the membrane tube pore size is 10 μm, the continuous phase flow rate is 1.2 m / s, and the ratio of the dispersed phase to the continuous phase is 20% (v / w).

[0036] (4) Under the conditions of heating at 60℃ and stirring at 250rpm, add 1.2mL of BDDE to the emulsion prepared in step (3) and continue heating and stirring for 60min.

[0037] (5) Add 328 mL of methanol to the emulsion prepared in step (4) and continue stirring at 250 rpm for 8 h under heating conditions at 60 °C to induce microsphere crystallization and solidification.

[0038] (6) After stopping stirring and allowing the emulsion to stand and separate into layers in step (5), pour off the upper layer of liquid and collect the lower layer of microspheres. Add 100 mL of deionized water and wash for 15 min under ultrasonic and stirring conditions at 250 rpm. Repeat the washing process 3 times. Wash the microspheres 3 times with ethyl acetate, 3 times with petroleum ether, 3 times with ethyl acetate, and 3 times with deionized water using the same operation. After washing, the primary silk fibroin microspheres are obtained.

[0039] (7) Vacuum freeze drying: cool to 0℃ at 0.5℃ / min for 30 min; cool to -45℃ at 1℃ / min for 90 min; heat to -15℃ and sublimate under vacuum of 5Pa for 12 h; heat to 20℃ and dry under vacuum of 5Pa for 26 h to obtain silk fibroin microspheres.

[0040] Example 2

[0041] The difference between this embodiment and embodiment 1 is that the ratio of dispersed phase to continuous phase in step (3) is 33% (v / w), while other steps and parameters remain unchanged.

[0042] Example 3

[0043] The difference between this embodiment and embodiment 1 is that the membrane tube pore size in step (3) is 20 μm, while the other steps and parameters remain unchanged.

[0044] Example 4

[0045] The difference between this embodiment and embodiment 1 is that the continuous phase flow velocity in step (3) is 1.0 m / s, while the other steps and parameters remain unchanged.

[0046] Example 5

[0047] The difference between this embodiment and embodiment 1 is that the membrane pressure in step (3) is 2.5 kPa, while the other steps and parameters remain unchanged.

[0048] Example 6

[0049] The difference between this embodiment and embodiment 1 is that the amount of BDDE added in step (4) is 0.6 mL, while the other steps and parameters remain unchanged.

[0050] Example 7

[0051] The difference between this example and Example 1 is that the amount of methanol added in step (4) is 164 mL, and other steps and parameters remain unchanged.

[0052] Comparative Example 1 The difference between this comparative example and Example 1 is that the enzyme digestion treatment in step (1) is omitted, and the non-enzymatically digested silk fibroin raw material is obtained by vacuum freeze-drying after purification, and other steps and parameters remain unchanged.

[0053] Comparative Example 2 This comparative example uses a mechanical emulsification method to prepare microspheres, specifically: (1) Dissolve 150 g of anhydrous sodium carbonate in 15 kg of water, and after boiling, add 150 g of silk, and cook for 45 min to obtain degummed silk. The degummed silk is fished out, washed with water for 3 times, and then dried; 50 g of dried degummed silk is dissolved in 500 mL of 9.3 M LiBr solution, filtered, and purified by molecular weight screening to obtain a regenerated silk fibroin aqueous solution with a weight average molecular weight of 100 kDa-250 kDa, and a trypsin solution of 3 mg / g is mixed with the same volume, reacted at 37°C for 20 h, and the enzyme is inactivated by heating at 100°C for 10 min. Centrifugation at 5000 rpm for 10 min removes the supernatant, and the modified silk fibroin precipitate raw material is obtained after drying.

[0054] (2) Dissolve 9.0 g of silk fibroin precipitate in 60 mL of 9.3 M LiBr aqueous solution until completely dissolved to obtain a 15% (w / v) silk fibroin solution as the dispersed phase.

[0055] (3) At 45°C, mix liquid paraffin, Span 80 and Tween 80 in a mass ratio of 100:7.5:2.5 to obtain a mixed oil phase.

[0056] (4) Add 2 mL of the dispersed phase at 45°C dropwise to 10 mL of the mixed oil phase under stirring with a syringe, and continue stirring for 40 min after the addition is completed; the stirring speed is 300 rpm.

[0057] (5) After washing with ethanol and pure water in turn, vacuum freeze-drying is carried out in the same process as in Example 1 to obtain silk fibroin microspheres.

[0058] Comparative Example 3 The difference between this comparative example and Example 1 is that the pre-freezing treatment in step (7) is cooled to -45°C at a rate of 0.3°C / min, and other steps and parameters remain unchanged.

[0059] Comparative Example 4 This comparative example uses SPG membrane emulsification + traditional crystallization induction method, specifically: Steps (1)-(3) are the same as in Example 1; (4) The pretreatment solution was prepared by adding 10% methanol to the emulsion prepared in step (3), and then adding 1% gelatin solution at a volume ratio of 1% gelatin solution: pretreatment solution of 2:1. After mixing evenly, the mixture was placed in a -80°C refrigerator for 48 hours, then taken out and thawed in a 37°C water bath. After ultrasonic treatment, centrifugation, and washing, the sample was vacuum freeze-dried according to the parameters in step (7) of Example 1 to obtain the silk fibroin microsphere sample.

[0060] Test Example 1: Microsphere Particle Size Detection An appropriate amount of silk fibroin microspheres was placed in a 5 mL test tube, 2 mL of 0.5% Tween 80 solution was added, and the microspheres were shaken to ensure they were fully wetted by the dispersion medium. The stirrer and ultrasonic wave were turned on, and the sample was added to a particle size analysis sample pool containing 150 mL of deionized water. The stirring and ultrasonic wave were turned on, and the D50, D10, and D90 were measured when the transmittance was between 70% and 90%. The particle size span of the microspheres was calculated according to the formula: Span = (D90-D10) / D50.

[0061] Wherein, D50 is the median particle size, representing the particle size of 50% of the microspheres; D90 represents the particle size of 90% of the microspheres; D10 represents the particle size of 10% of the microspheres; and Span represents the span of the microsphere particle size. The smaller the Span value, the narrower the distribution of the microsphere particle size. The particle size parameters of the microspheres obtained in the examples and comparative examples are shown in Table 1.

[0062] Table 1

[0063] From Table 1, it can be seen that the size of the microspheres prepared in Examples 1-7 meets the requirements, and the Span value is low, and the microspheres have good particle size uniformity. In Example 1, the microspheres prepared have a D50 of about 35.8 μm, and a Span value of 1.26. In Example 2, the ratio of the dispersed phase to the continuous phase is increased from 20% (v / w) to 33.3% (v / w) compared with Example 1, and the D50 of the microspheres increases to 40.3 μm, which is due to the increase in the ratio of the dispersed phase, which causes some silk fibroin emulsion droplets to fuse after emulsification. In Example 3, the pore size of the SPG membrane tube is increased to 20 μm compared with Example 1, and the D50 of the microspheres significantly increases to 62.3 μm, which shows that the pore size of the membrane tube is the most significant factor affecting the particle size of the microspheres, and it directly determines the size of the silk fibroin emulsion droplets after emulsification, and the particle size of the microspheres can be adjusted by adjusting the pore size. In Example 4, the flow rate of the continuous phase is reduced to 1.0 m / s compared with Example 1, and the D50 of the microspheres increases to 37.2 μm, and the flow rate mainly affects the fluid drag force of the continuous phase on the emulsion droplets and affects the particle size of the microspheres, and the fluid drag force of the continuous phase on the emulsion droplets decreases with the decrease of the flow rate of the continuous phase, and the dispersed phase emulsion droplets are more difficult to be sheared off from the membrane pores, so the particle size of the microspheres is larger. In Example 5, the pressure across the membrane is increased to 2.5 kPa compared with Example 1, and the D50 of the microspheres increases to 43.2 μm, which is due to the increase in the pressure across the membrane, and the speed of the dispersed phase being extruded through the membrane pores increases under the action of the pressure, and the volume of the emulsion droplets formed at the outlet of the membrane pores is larger, so the particle size of the prepared microspheres is larger. In Examples 6-7, the addition amount of the crosslinking agent and the crystallization inducer is adjusted within a proper range compared with Example 1, and the results show that the D50 of the prepared microspheres is similar to that of Example 1.

[0064] In Comparative Example 1, microspheres were prepared using silk fibroin raw materials that have not been subjected to enzyme cutting and contain hydrophilic non-crystalline regions, and the detection showed that the D50 of the prepared microspheres was about 48.3 μm, which was significantly larger than that of the microspheres prepared using enzyme-cut silk fibroin raw materials in Example 1. This may be due to the fact that the silk fibroin molecules containing hydrophilic non-crystalline regions cannot form a dense structure when induced to crystallize, and the molecular arrangement is loose, resulting in a larger particle size of the microspheres and a more uneven particle size distribution, and the Span value is as high as 1.48. In Comparative Example 2, the mechanical emulsification method was used, and the particle size of the microspheres was uneven, and the Span value was as high as 1.5 or more. In Comparative Example 4, silk fibroin microspheres were prepared using the membrane emulsification method disclosed in the present application and the traditional crystallization induction method, and the detected particle size of the silk fibroin microspheres reached 118.3 μm, which was significantly higher than that of each example, which was due to the fact that the traditional crystallization induction method cannot completely induce the crystallization of silk fibroin, resulting in the adhesion and fusion of the silk fibroin microspheres when 1% gelatin solution was added as a dispersant, and finally forming large-particle-size microsphere clumps.

[0065] Test Example 2: Microsphere morphology detection Figure 1 and Figure 2SEM images of microspheres prepared in Example 1 and Example 5, respectively, show that the microspheres have uniform particle size and smooth surface. Figure 3 The SEM image of the microspheres prepared in Comparative Example 1 shows that the surface of the microspheres is uneven, and there are some larger holes, which is presumably due to the fact that the silk fibroin molecules containing hydrophilic amorphous regions cannot form a dense structure when crystallization is induced, and the uneven crystallization of the molecules leads to the shrinkage of the surface of the finally prepared microspheres, resulting in wrinkles and even larger holes. Figure 4 The SEM image of the microspheres prepared in Comparative Example 2 shows that the microspheres prepared by pure mechanical emulsification have the largest particle size and the largest difference between the maximum and minimum particle sizes, and need to be further sieved for application, which significantly reduces the yield of qualified microspheres. Figure 5 The SEM image of the microspheres prepared in Comparative Example 3 shows that there are a large number of cracks and wrinkles on the surface of the microspheres, presumably due to the damage to the surface morphology of the microspheres caused by large ice crystals formed by slow freezing. Figure 6 The SEM image of the microspheres prepared in Comparative Example 4 shows that the prepared microspheres have a particle size generally greater than 100 μm, and there is a significant problem of agglomeration of microspheres of different sizes, presumably due to the fact that the traditional induced crystallization method cannot completely induce the crystallization of silk fibroin, resulting in the adhesion and fusion of the silk fibroin microspheres when 1% gelatin solution is added as a dispersant, and finally forming large-particle-size microsphere blocks, which is consistent with the particle size test results.

[0066] Test Example 3: Crystallinity detection of microspheres The crystallinity of the microsphere samples of different examples and comparative examples was analyzed using the ATR mode of the infrared spectrometer, and the proportion of β structure in the secondary structure of silk fibroin molecules was determined by Fourier self-deconvolution of the amide I band (1585-1710 cm -1 ) using the OMNIC software, and the crystallinity was obtained by the proportion of β structure, and the results are shown in Table 2.

[0067] Table 2

[0068] As shown in Table 2, the microspheres obtained in Examples 1-7 have good crystallinity. Among them, the crystallinity of the microspheres obtained in Examples 1-5 is between 49.3%-55.8%, and there is no big difference. After appropriately reducing the crosslinking agent and the crystallization inducer in Examples 6-7, the crystallinity is appropriately reduced, which is presumably due to the fact that the use of the crosslinking agent can significantly shorten the distance between the molecular chains in the crystalline region, and promote the crystallization between the silk fibroin molecules; the crystallization inducer mainly destroys the hydration layer on the surface of the silk fibroin molecules, promotes the formation of hydrogen-bonded β-sheet structure between the silk fibroin molecules, and thus induces crystallization.

[0069] The crystallinity of the microspheres of Comparative Example 1 was significantly reduced to 28.3%, which can be due to the non-enzymatic cut silk fibroin molecules containing hydrophilic non-crystalline regions hindering the formation of beta-sheet structure during crystallization, ultimately resulting in low crystallinity. The microspheres prepared in Comparative Example 2 using a pure mechanical emulsification method and not induced to crystallize by a crosslinking agent and a crystallization inducer had a crystallinity of 22.3%. Comparative Example 3 used a different freeze-drying process to dry the microspheres, and the crystallinity slightly decreased to 46.3%. The silk fibroin microspheres prepared in Comparative Example 4 using the film emulsification method disclosed in the present application and the conventional crystallization induction method had a crystallinity of 31.2%, which was significantly lower than that in the examples, indicating that the conventional crystallization induction method was not sufficient to induce the silk fibroin to fully crystallize.

[0070] Test Example 4: Microsphere Swelling Rate Test The swelling rates of the microsphere samples of the examples and comparative examples were tested, and the results are shown in Table 3. The specific testing process is as follows: take 2.5 mL EP tubes, weigh and record as W0. Take about 0.5 g of dried silk fibroin microsphere sample and add it to the EP tube, weigh and record as W1. Add 1.5 mL of normal saline to the centrifuge tube to resuspend the microspheres, and incubate at 37°C overnight. After completion, centrifuge at 10000 rpm for 5 min, discard the supernatant, and then weigh the centrifuge tube together, and record as W2. The microsphere swelling rate calculation formula is as follows: Microsphere swelling rate % = (W2-W0) / (W1-W0) x 100%.

[0071] Table 3

[0072] As can be seen from Table 3, the microspheres of Examples 1-7 had a low swelling degree, between 8.6% and 20.4%. The microspheres prepared in Comparative Example 1 using non-enzymatic cut silk fibroin raw materials containing hydrophilic non-crystalline regions had a swelling degree of 25.8%; the microspheres with the highest swelling degree were in Comparative Example 2, reaching 37.2%.

[0073] Test Example 5: Microsphere Degradation Test Take a 2.5 mL EP tube with a weight of M0, fill it with about 50 mg of microspheres prepared in Example 1, Comparative Example 1, and Comparative Example 2, weigh the microspheres + EP tube weight M1, set 3 parallel samples for each group, and take 5 samples for each sample. Add 1 mL of PBS buffer containing 1 U / mL protease K (pH = 7.4), place it in a 37°C shaker at 60 rpm for a total of 21 days, take out the EP tube every 3 days, centrifuge at 10000 rpm for 5 min to discard the supernatant, and add a new prepared protease K solution. Take one EP tube from each parallel sample in each group on the 3rd, 6th, 9th, 15th, and 21st day, centrifuge at 4500 rpm for 5 min, discard the supernatant, and then add purified water to wash twice, centrifuge at 4500 rpm for 5 min after each washing, and then freeze-dry. Weigh the microspheres + EP tube weight M2 after freeze-drying, and calculate the silk fibroin microsphere degradation rate according to the following formula: Microsphere degradation rate % = (M2-M1) / (M1-M0) x 100%.

[0074] Figure 7 is the degradation curve of the microspheres of Example 1, Comparative Example 1-2, and it can be seen that the degradation rate of Example 1 is significantly lower than that of Comparative Example 1-2, which is due to the higher crystallinity of the microspheres obtained in Example 1. From the degradation experiment results, it can be seen that the microspheres prepared by the present application have a longer degradation time and higher anti-enzymatic ability.

[0075] The present application has been described in detail in combination with specific embodiments and exemplary examples, but these descriptions cannot be understood as limiting the present application. Those skilled in the art understand that the technical solutions and embodiments of the present application can be variously replaced, modified, or improved without deviating from the spirit and scope of the present application, and these all fall within the scope of the present application. The scope of protection of the present application is subject to the appended claims.

Claims

1. A method for preparing silk fibroin microspheres with uniform particle size, characterized in that, Includes the following steps: S1. Take the regenerated silk fibroin solution, digest it with trypsin to obtain modified silk fibroin precipitate, dissolve it in an aqueous solution of β-sheet inhibitor to obtain silk fibroin solution, and use it as the dispersed phase; S2. Emulsification is performed using an external pressure membrane emulsifier to disperse the dispersed phase in a continuous phase, thereby obtaining an emulsion containing silk fibroin droplets. S3. Add a cross-linking agent to the emulsion to carry out the cross-linking reaction of silk fibroin, and then add a crystallization inducer to induce the crystallization of silk fibroin to obtain primary silk fibroin microspheres. S4. The primary silk fibroin microspheres are freeze-dried under vacuum to obtain silk fibroin microspheres.

2. The method for preparing uniform-sized silk fibroin microspheres as described in claim 1, characterized in that, In S3, the crosslinking agent is one or more of butanediol glycidyl ether, divinyl sulfone, and epoxy-polyethylene glycol-epoxy groups; And / or, the volume ratio of the crosslinking agent to the dispersed phase is 0.5%-5%; And / or, the conditions for the crosslinking reaction are: temperature 30-80℃, stirring speed 150-500rpm, and time 20-90min.

3. The method for preparing uniform-sized silk fibroin microspheres as described in claim 1, characterized in that, In S3, the crystallization inducer is one or more of methanol, ethanol, isopropanol, n-butanol, tert-butanol, acetone, formic acid, N,N-dimethylformamide, dimethyl sulfoxide, chloroform, and ethylene oxide. And / or, the volume ratio of the crystallization inducer to the dispersed phase is 100%-800%; And / or, the conditions for inducing silk fibroin crystallization are: temperature 30-80℃, stirring speed 150-500rpm, and time 2-10h.

4. The method for preparing uniform-sized silk fibroin microspheres as described in claim 1, characterized in that, In S2, the membrane tube of the external pressure membrane emulsifier is an SPG membrane with a pore size of 5-40 μm; And / or, the emulsification parameters are: temperature 5-30℃, continuous phase flow rate 0.5-1.5m / s, membrane pressure 0.5kPa-5kPa, and the volume mass ratio of dispersed phase to continuous phase is 10%-50%, in mL / g.

5. The method for preparing uniform-sized silk fibroin microspheres as described in claim 1, characterized in that, In S2, the mass-to-volume ratio of silk fibroin to aqueous solution in the dispersed phase is 2%-25%, in g / mL; And / or, the continuous phase is one or more of the following: light liquid paraffin, heavy liquid paraffin, soybean oil, castor oil, palm oil, olive oil, sesame oil, corn oil, lecithin, petroleum ether, n-hexane, n-heptane, petrolatum, silicone oil, and ceresin. And / or, the continuous phase further includes a surfactant at a mass concentration of 0.5%-3%.

6. The method for preparing uniform-sized silk fibroin microspheres as described in claim 1, characterized in that, In step S4, the vacuum freeze-drying includes the following steps: Pre-cool to 0-4℃ at a rate of 0.4-1℃ / min for 20-40 min; pre-freeze to -50℃ ~ -40℃ at a rate of 0.9-1.2℃ / min for 60-120 min; heat to -20℃ ~ 0℃ and sublimate under a vacuum of 0-30Pa for 10-24 h; heat to 0-30℃ and dry under a vacuum of 0-30Pa for 5-30 h.

7. The method for preparing uniform-sized silk fibroin microspheres as described in claim 1, characterized in that, In S1, the weight-average molecular weight of the regenerated silk fibroin is 50kDa-250kDa.

8. The method for preparing uniform-sized silk fibroin microspheres as described in claim 1, characterized in that, In S1, the β-sheet inhibitor is one or more of LiBr, NaSCN, ZnCl2, and CaCl2; And / or, the concentration of the β-sheet inhibitor in the aqueous solution of the β-sheet inhibitor is 4-9.3M.

9. A method according to any one of claims 1-8 for preparing silk fibroin microspheres.

10. The application of the silk fibroin microspheres according to claim 9 in medical products and cosmetic products.

Citation Information

Patent Citations

  • Preparation method of silk fibroin nanospheres

    CN119331274A

  • Method for purifying silk fibroin

    CN103613652A

  • Preparation method of gelatin drug-loaded microspheres with controllable granularity and single distribution as well as product and application of gelatin drug-loaded microspheres

    CN115414522A

  • Silk fibroin microspheres and preparation method thereof

    CN118420936A

  • Preparation method of silk fibroin composite freeze-drying filler with controllable molecular weight

    CN119746158A

Cited By

  • Composite absorption pad and preparation method thereof

    CN121818236A

  • Silk fibroin composite microsphere, gel, preparation method and application

    CN122057079A